Evaluation of the Effect of Clinician-Patient Relationship Protocol on Vital Sign (Pulse and Blood Pressure) Control in Emergency Endodontic Patients - Maryam Kazemipoor; Mostafa Mehraban; Fatemeh Owlia (Mashhad University of Medical Sciences, 2023)
Introduction: Monitoring of vital signs in endodontic emergency patients is of significant importance. Stress as a primary concern in root canal therapy should be controlled during the treatment procedures. The present study aimed to evaluate the effect of patient-clinician relationship protocol on controlling patients' vital signs.Materials and Methods: This interventional study investigated 70 endodontic emergency patients with an age range of 18-60 years in 2019. The patients were divided into two groups of 35. The treatment procedure in the experimental group was accomplished with an intervention of patient-clinician relationship protocol. Blood pressure (systolic and diastolic) and heart rate of patients in five stages before local anesthesia, at the time of local anesthesia, during tooth drilling, after treatment, and one week after the termination of the treatment were measured as a baseline. Data were analyzed using SPSS software (version 22) through the Chi-square and independent statistical t-test. The significant level was set at 0.05.Results: Based on the results, patients' age, gender, history of root canal therapy, pulpal and periapical disease, as well as the type of local anesthesia, were not regarded as interfering factors in changing the vital signs among patients. In contrast, pain intensity interfered with changes in vital signs among patients. Patient-clinician relationship protocol significantly reduced the systolic blood pressure at the time of local anesthesia, during tooth drilling, and after treatment. Moreover, patient-clinician relationship protocol also significantly reduced diastolic pressure at the time of local anesthesia, during tooth drilling, and after treatment. Considering heart rate, the patient-clinician relationship protocol significantly reduced heart rate only during tooth drilling.Conclusion: Considering the results of the present study, the application of patient-clinician relationship protocol significantly affects the control of vital signs in emergency endodontic patients.